Viability and biological properties of probiotic vaginal lactobacilli after lyophilization and refrigerated storage into gelatin capsules - Zarate, Gabriela del Valle (2006)
In the present study we investigated the survival and stability of probiotic properties of three vaginal lactobacilli after freeze drying with the addition of individual and combined compounds commonly used as pharmaceutical excipients and/or starters cryoprotectants, and subsequent refrigerated storage during 15 months. Lactobacilli, suspended in lactose, skim milk, ascorbic acid and combinations of them, were freeze-dried, packed into gelatin capsules and stored at 5 °C under darkness. At regular intervals throughout storage, freeze-dried samples were rehydrated and viability, adhesion to vaginal epithelial cells and antimicrobial activities were evaluated. The Lactobacillus tested conserved high viability up to 12 months in capsules containing ascorbic acid or combined excipients whereas lyophilization and storage with lactose or skim milk significantly decreased their survival. Abilities to produce lactic acid, H2O2 and bacteriocin were affected to different extents depending on the condition assayed. Lyophilization and storage also reduced the capacity of lactobacilli to adhere to vaginal epithelial cells but this property was partially restored after the first subculture in broth. The results obtained suggests that suitable selection of excipients that could also act as protecting agents of LAB during storage should be a valuable step in the development of a probiotic formulation with a stable shelf-life.